Virtual Expo Using Inflatable Stage Covers for SMEs as an Online Exhibition Solution During the Covid-19 Pandemic (International Conference of Graduate School on Sustainability (ICGSS), 2020)
Global economic competition is a challenge for SME creative products. The problem that is often faced is that the marketing media will not influence consumer interest in obtaining SME products. Marketing through exhibition is the most effective means of selling SME products. However, the COVID-19 outbreak that broke out in early 2020 had a significant impact on the lives of people around the world. Virtual exhibitions can be a solution in the midst of crowd restrictions during large-scale social restrictions. Virtual exhibition is an event that can be watched on computers and cellphones using the internet anywhere and anytime directly (life streaming) and can be watched the recordings via the Youtube channel. The virtual exhibition was held in a short time, therefore it required a portable stand and stage infrastructure that could be built and dismantled quickly and concisely. Virtual exhibition and workshop for knitting handicrafts entitled "Virtual Expo and Workshop for SME Malang City has been successfully held at Merdeka University Malang within 1 day involving 6 creative SME communities in Malang, applying a portable stage and inflatable stage roof with independent photovoltaic solar energy. A portable stage can be built in 2 hours and the inflatable stage roof can be built in just 10 minutes, requiring a total of 4 people. The results obtained from the implementation of virtual expo and workshop were that during the Covid-19 Pandemic, creative product SMEs were still able to carry out virtual exhibitions that could be watched live (live streaming) or view edited video recordings via Youtube channels using computers or cellphonesKeywords: Virtual Expo, SME, inflatable cover stage, covid-19